Skrining Fitokimia dan Uji Efektivitas Tepung Biji Kelor (Moringa oleifera L.) dalam Menurunkan Kadar Kolesterol Total Darah Mencit Jantan - Nurliana, Nurliana; Rahman, Nurdin; Ratman, Ratman (Jurnal Akademika Kimia, 2018)
The aim of the study was to determine phytochemical compounds levels in Moringa seeds and determine the effective dose of moringa seed flour in lowering total cholesterol blood levels of mice. Qualitative test of phytochemical compounds in moringa seed flour was done using specific reagents. The effect of moringa seed flour in lowering total cholesterol blood levels was performed in 18 male mice divided randomly into 6 groups, i.e P1 as the negative control group, P2 as the positive control group by giving simvastatin, P3 as the test group with a dose of 0.14 g/kg BW/day, P4 as the test group with a dose of 0.28 g/kg BW/day, P5 as the test group with a dose of 0.42 g/kg BW/day, and P6 as the test group with a dose of 0.56 g/kg BW/day. P1 to P6 were given propylthiouracilin conjunction with a suitable treatment of the group. Data were analyzed with One-way ANOVA and Duncan's post hoc tests at 95% significant level. Results showed that moringa seed flour contained positively of flavonoids and saponins. Results analysis of changes on the total cholesterol levels between groups with One-way ANOVA test showed a significant difference (p = 0.002), where Fcount value=7.476 > Ftable value=3.11. The group with the provision of 0.42 g/kg BB/day of moringa seed flour performed the most effective influence in lowering total cholesterol blood levels of male mice which amounted to 34.33 mg/dL or 18.66%.